An in situ technique for (U–Th–Sm)/He and U–Pb double dating. Issue 7 (24th July 2015) - Evans, N. J.; McInnes, B. I. A.; McDonald, B.; Danišík, M.; Becker, T.; Vermeesch, P.; Shelley, M.; Marillo-Sialer, E.; Patterson, D. B.
<x xml:space="preserve">Abstract</x> New in situ (U–Th–Sm)/He and U–Pb zircon double dating method replicates results obtained using conventional methods at the Ellendale diamond occurrence.